2007
DOI: 10.2166/wh.2007.010b
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen and indicator variability in a heavily impacted watershed

Abstract: Water samples were collected from 36 locations within the Grand River Watershed, in Southwestern Ontario, Canada from July 2002 to December 2003 and were analyzed for total coliforms, fecal coliforms, Escherichia coli, Escherichia coli O157:H7, and thermophilic Campylobacter spp. A subset of samples was also analyzed for Cryptosporidium spp., Giardia spp., culturable human enteric viruses, and Clostridium perfringens. Storm and snowmelt events were sampled at two locations including a drinking water intake. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 31 publications
5
61
1
Order By: Relevance
“…Both gene targets were detected most frequently at the Canagagigue Creek sampling location. The Canagagigue Creek subwatershed is located in a region with the highest livestock density in the watershed (Dorner et al 2007) and where estimates for daily manure production were also highest (Dorner et al 2004). for Yersinia in water also noted a higher rate of isolation during colder months of the year (Meadows & Snudden 1982;Fukushima et al 1984).…”
Section: Confirmation Of Quantitative Pcr Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both gene targets were detected most frequently at the Canagagigue Creek sampling location. The Canagagigue Creek subwatershed is located in a region with the highest livestock density in the watershed (Dorner et al 2007) and where estimates for daily manure production were also highest (Dorner et al 2004). for Yersinia in water also noted a higher rate of isolation during colder months of the year (Meadows & Snudden 1982;Fukushima et al 1984).…”
Section: Confirmation Of Quantitative Pcr Resultsmentioning
confidence: 99%
“…It provides part of the drinking water supply for approximately 500,000 people, and is also used for recreational activities (Dorner et al 2004). This system is one of the most heavily impacted watersheds in Canada, receiving inputs from both agricultural and urban activities (Dorner et al 2004), and a number of enteric pathogens typically found in surface waters have been previously detected (Dorner et al 2007). This research provides information for an emerging waterborne pathogen that is not well characterized in water sources.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies (most of which were small and of short duration) have reported conflicting results regarding the value of detecting E. coli to predict Campylobacter sp. presence (4,9,11,12,16,17,21,27,29,31,38,40,43,48). We report here a large study that analyzed 2,471 water samples from 32 different sites over 2 years to resolve this question.…”
mentioning
confidence: 96%
“…Turbidity measures the water clarity and is due to suspended solid materials such as clay, silt, colloidal organic matter, planktons, and other organisms (Dorner et al 2007). The turbidity average values varied from 5.4 ± 1.08 to 14.3 ± 3.10 and from 7.4 ± 1.61 to 47.3 ± 8.12 NTU during PRM and POM seasons, respectively.…”
Section: Resultsmentioning
confidence: 99%